Influences of rock microstructure on acid dissolution at a dolomite surface. (March 2022) - Xu, Peng; Sheng, Mao; Lin, Tianyi; Liu, Qing; Wang, Xiaoguang; Khan, Waleed Ali; Xu, Quan
Highlights: The static surface acidification experiment integrating SEM microstructure mapping and micromechanical test was proposed to understand the effects of rock microstructure on the fracture etching of geothermal dolomite reservoir. The crystal structure and pores distribution highly influence on the fracture etching and the ultimate conductivity of geothermal dolomite reservoir. Abstract: Acid etching in a naturally fractured carbonate formation is one of the most significant mechanisms to enhance the fluid conductivity in fractures. In this paper, an acid dissolution experiment has been employed to understand the influence of rock microstructure on the acid etching involving reaction rate, the morphology of acid corrosion, and the embedding strength of a fracture surface. Three typical dolomite samples with almost the same mineral composition but distinct microstructures were selected from the Wumishan Geothermal carbonate formation that is composed of dolomudstone, algal dolomudstone, and silt-to-fine crystalline dolostone. A couple of measurement approaches including the thin section, SEM, 3D laser scanning, and nano indentation tests were used to observe and quantify the microstructures, reaction rate, and embedding strength of the fracture surface. Microstructure characterization indicates that the dolomudstone contains much finer crystal particles and a loose microstructure compared to other two samples. On the contrary, the silt-to-fine crystalline dolostone reserves coarse crystal particles and a tight microstructure. The structure of algal dolomudstone falls in between those two mentioned cases. Results of acid dissolving reveal that rock microstructures offer control over the acid-rock reaction of dolomite. Specifically, the loose microstructure of dolomite depicts a fast acid reaction, a rough surface, but weak embedding strength, while the compact microstructure behaves as a slow acid reaction, a uniform etching, and with a strong embedding strength. The knowledge obtained from this study is valuable to optimize the acid dissolution strategy from the view of the microstructure analysis.